Genetic differentiation between wildtype and spotted swamp buffaloes (Bubalus bubalis) of Indonesia based on ISSR and RAPD markers - Widya Putra; Salah Faraj; Novi Adiningsih; Abdullah Baharun; Hartati Hartati; Aprisal Aprisal; Tulus Maulana; Syahruddin Said; Hasbi Hasbi; Petra Sitanggang (Iraqi Journal of Veterinary Sciences, 2025)
The swamp buffaloes (Bubalus bubalis) are an important livestock that is used for draught, meat production, and cultural tradition ceremonies in Indonesia. This study aimed to characterize the wildtype and spotted buffaloes based on inter-simple sequence repeat (ISSR) and random amplified polymorphic DNA (RAPD) markers. A total of twenty-two buffaloes (13 wildtype and nine spotted) were used for the experimental animals. Two ISSR primers (P01, P02) and three RAPD primers (SRILLS-2, SRILLS-5, SRILLS-6) were assessed to discriminate between the two types of buffalo. Results showed that the ISSR primers had a higher polymorphic informative content (PIC) value than RAPD primers. Therefore, P01 had the highest polymorphic informative content (PIC) value (0.412) and SRILLS-5 as the lowest (0.063). Shannon’s diversity index (I) value in both techniques was>1.00 and indicating a various fragment sizes resulted from each primer. However, the RAPD technique can discriminate between two types of buffalo better than the ISSR technique. In the pool animals, haplotype one of SRILLS-6 (16 heads) was more frequent than other haplotypes and followed by haplotype two of P02 (14 heads). Despite this, two types of swamp buffalo in the present study can also be discriminated with a combination of ISSR and RAPD techniques accurately. In conclusion, the ISSR and RAPD primers in the present study can be used as genetic markers to differentiate swamp buffaloes of Indonesia.